Si-RF Technology - Karmakar, Ayan; Singh, Kamaljeet (Springer Nature Singapore : Imprint: Springer, 2019)
This book discusses the recent research developments of various passive microwave circuits on silicon substrate and demonstrated operations catering for multiple frequency bands. It covers the design, modelling, process fabrication and characterization aspects with practical examples. The book will be of use to researchers and engineers working in the field of RF or microwave engineering, who can use the techniques and approaches effectively without having to refer to multiple sources. .